EVA - budowa systemu zarządzania przez wartość - Radawiecka, Ewa (EVA - Building Management System Trough Value, 2007)
Economic Value Added - EVA is a category which can defined as a variance between a realized profit and a capital cost, which is necessary for obtaining this profit. The main advantage that accounts for the development of this concept is an increase in value for stockholders. This is a base for complex planning system and a financial statement and consequently it constitutes the main link connecting economic results of the company with premium system for all employees, building up the motivation for realization of established aims. The initiation of a management system that is based on the Economic Value Added - EVA allows to multiply the wealth of the owners, clients and the people who manage the company and other members of the association as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 424-433